Adaptive Multi-mode Combination for Magnetoelectric Sensors Based on the Delta-E Effect. (2015) - Reermann, Jens; Schmidt, Gerhard; Zabel, Sebastian; Faupel, Franz
Abstract: Recently, magnetoelectric sensors have gained importance in medical applications. Among several sensor types microelectromechanical magnetic field sensors are a promising option since they can be manufactured in a very small fashion and can operate at room temperature. In this contribution we present a new readout scheme for such sensors that simultaneously uses amplitude and phase information of a multitude of mechanical modes of a single sensor. The sensors are based on the delta-E effect. All extracted information is optimally combined in order to get a sensor output signal with maximum signal-to-noise ratio (SNR). First measurements have shown very promising results.